Efektivitas Convention on International Trade in Endangered Species in Wild Fauna and Flora (CITES) di Indonesia Studi Kasus : Penanganan Perdagangan Gading dan Produknya di Nusa Tenggara Timur - D, Putri Lia Alfiani; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The Convention on International Trade in Endangered Species of Wild and Flora (CITES) is an environmental convention to regulate the trade in protected wild flora and fauna. Elephant is included in the Appendix I which is trade for commercial purposes is prohibited. Indonesia is also one of the countries that ratified CITES which should implement the conventions. Yet, at the sub-national level, the people of East Nusa Tenggara still have not change their behavior which contrasts with the intention to comply the convention. Trade of elephant ivory are still practice in East Nusa Tenggara for customary purposes and for commercial purposes. The aims of this research is to answer why ivory trade still happened in East Nusa Tenggara even even though Indonesia has ratified CITES. This research use compliance theory by Robert B. Mitchell to analyzing the effectiveness of the regime through three indicators i.e. output, outcomes, and impact. The results of this research indicate that the ivory trade East Nusa Tenggara community's due to the effectiveness of CITES in Indonesia has not been realized perfectly. The form of the regulation has been realized but behavior change in NTT society has not yet occurred. This is caused by factors of incapacity as well as lack of relevant administrative factors.